Acute pancreatitis after nitrous oxide abuse: A case report. Issue 1 (1st December 2022) - Chen, Shanshan; Guo, Linjie; Wang, Yufang
Abstract: The recreational use of nitrous oxide (N2 O) is sharply increasing among young adults. N2 O abuse can cause serious complications. However, the association between acute pancreatitis and N2 O is rarely reported. Here we report a case of a young and previously healthy female with widespread cutaneous lesions, neurologic symptoms, and abdominal pain. Acute pancreatitis was the patient's primary diagnosis when she was admitted to the gastroenterology unit. We added the diagnosis of N2 O intoxication after an additional inquiry into the patient's personal history revealed that she had abused N2 O for 1 month. With the application of mecobalamin and other symptomatic treatments, the symptoms and laboratory indexes improved gradually. In this case, we highlight that acute pancreatitis may be a rare complication induced by N2 O. Abstract : We report a young and previously healthy female who was first admitted to the gastroenterological department with acute pancreatitis and was finally diagnosed with N2 O intoxication. Thus, we found that acute pancreatitis may be a rare complication in N2 O intoxication.